Species Diversity of Epiphytes Lichens in Kopeng Treetop Adventure Park and Umbul Sanga, Mount Merbabu National Park - Untari, Ludmilla (Berkala Ilmiah Biologi, 2025)
Mount Merbabu is one of the national parks in Indonesia, located in the Mount Merbabu area. Mt. Merbabu is located in three regencies, Magelang Regency, Boyolali Regency and Semarang Regency. This national park area is a protected forest area, which is an important habitat for the diversity of flora and fauna. One of the important groups of organisms found in the area is lichens. The lichens are an organism that is the result of a symbiosis between algae and fungi and has a very high diversity. The objective of this study is to determine the diversity of lichens species in Kopeng Treetop Adventure Park and Umbul Sanga, Mount Merbabu National Park. Kopeng Treetop Adventure Park and Umbul Sanga are areas within Mount Merbabu National Park, which is a tourist area. Sampling was carried out using the purposive random sampling method, then identification was carried out based on macroscopic and microscopic characteristics as well as chemical characteristics using a simple spot test. The identification results showed a number of 19 species, namely Crytothecia sp., Diploicia canescens, Graphis scripta, Hypotrachyna britannica, Hypotrachyna revoluta, Lecanora conizaeoides, Lecanora expallens, Lepraria lobificans, Lepraria neglecta, Lepraria nivalis, Candelaria sp., Parmelia sp., Parmelia sulcata, Parmelia tiliacea, Parmotrema perlatum, Parmotrema crinitum, Platismatia glauca, and Xanthoparmelia mougeotii. A description of each species is presented in this article.